Folic Acid Supplementation Attenuates Chronic Hepatic Inflammation in High‐Fat Diet Fed Mice. Issue 7 (25th September 2018) - Sid, Victoria; Shang, Yue; Siow, Yaw L.; Hewage, Susara Madduma; House, James D.; O, Karmin
Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common form of chronic liver disease worldwide. Hepatic inflammation is an important pathogenic mediator of NAFLD. There is currently no pharmacological agent approved for the treatment of NAFLD. Folic acid is a water‐soluble B vitamin that has been shown to have lipid‐lowering and antioxidant effects. The objective of this study was to investigate the effect of folic acid supplementation on hepatic inflammation and to identify the underlying mechanisms. Male C57BL/6 J mice were fed a control diet (10% kcal fat), a high‐fat diet (HFD) (60% kcal fat), or a HFD supplemented with folic acid (26 mg/kg diet) for 8 weeks. HFD feeding led to increased body mass gain, lipid accumulation, activation of transcription factor nuclear factor‐κB (NF‐κB), and elevation of inflammatory cytokine gene expression in the liver. Folic acid supplementation attenuated hepatic lipid accumulation and aggregation of inflammatory foci induced by HFD feeding. This was associated with a significant reduction of NF‐κB activation and inflammatory cytokine expression. These results suggest that the hepatoprotective effect of folic acid in NAFLD may be attributed, in part, to its anti‐inflammatory action.